The concept of aesthetic value in contemporary criticism (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
This research attempts to address the concept of aesthetic value in contemporary criticism, analyze the opinions of the most important aesthetic critics who presented this concept, explain the relationship between aesthetic value and standard, and examine the applied aspect of aesthetics (aesthetic criticism), which is aware of aesthetic value in its literary formation from its various aspects.The research followed the descriptive approach as a procedural starting point to help it extrapolate critical aesthetic opinions. The research then studied the concept of value linguistically and terminologically, the concept of aesthetics linguistically and terminologically, and the criteria for aesthetic judgment. A presentation of the difference between values ​​and aesthetic categories, and finally a presentation of the concept of aesthetic criticism. The research came out with results, the most important of which is that aesthetic value is human agency in existence, which appears as a result of the relationship between the subject and the object, and through creative agency, aesthetic value can be achieved.